Avaliação de protocolo IoT e enlaces para comunicação V2V como suporte para ultrapassagens seguras em VANETs - Menezes, Sandro Andrade Monteiro (2023)
Based on the concepts of smart cities, Internet of Things - IoT and the resources that sensor networks can aggregate, this work is based on the evaluation of protocols and standards that can be used in vehicular networks (Vehicular Ad Hoc Networks – VANET) with the intention to carry out the analysis of three of the most promising application layer protocols IoT. The Constrained Application Protocol – COAP, Message Queuing Telemetry Transport - MQTT and IPv6 over Low power Wireless Personal Area Networks - 6LowPAN, these protocols have similar characteristics to each other, such as: energy efficiency, little need for processing and low latency, characteristics that are ideal for vehicular networks. In a scenario created by the Omnet++ simulator together with the frameworks Veins and Sumo, we tested the efficiency of these protocols on a Vanet network where latency, packet loss, jitter and throughput metrics were used. For analyses, was considered a model of vehicular overtaking, where the vehicles involved need to be aware of other vehicles nearby and be alert to their changes in route and speeds, this work was carried out using 802.11p networks together, the 802.15.4 and the promising 5G mobile network with the intention of verifying its efficiency in supporting drivers when overtaking where they do not have good visibility. In our simulations, the concepts of Overtaking Visibility Distance – DVU were applied, which are used by the National Department of Transport Infrastructure - DNIT and even even by the American Association of State Highway Transportation Officials – AASHTO. To the end of the simulations, which were based on a bidirectional highway scenario with vehicles in different directions and at random speeds, the superior efficiency of the MQTT protocol working in conjunction with the 5G mobile network standard. The efficiency of this combination was found in all metrics used, making it clear that the association between These two technologies constitute an excellent choice in favor of the concept of cities intelligent.